The Impact of Mathematics Teacher Quality on Student Achievement in Oman and Taiwan - Intisar Ambussaidi; Ya-Fei Yang (Association for Scientific Computing Electrical and Engineering(ASCEE), 2019)
Following the educational reform trend around the world, Oman and Taiwan emphasize on teacher quality to improve student learning. This study investigated the relationship between teacher quality and eighth graders mathematics achievement in Oman and Taiwan by utilizing TIMSS 2011 data. The research question examined to what extent teacher quality as defined by the measurable variables (teacher qualification, teaching practices and professional development) impacts student achievement in Oman and Taiwan. The study employed Ordinary Least Square (OLS) statistical analysis to examine the relationship between teacher quality and eighth-grade student math performance in both countries. The results show that teacher quality indicators in Oman and Taiwan have a positive impact on eighth graders mathematics achievement. However, teacher quality variables that influence student achievement in both countries vary depending on the education context, student characteristics and school factors. The study findings support policy intervention aimed at improving teacher quality and recommends providing more opportunities for participation in content-focused and pedagogical-focused professional development.